Analisis Kesalahan Siswa Kelas IX SMP Negeri 1 Loura dalam Menyelesaikan Soal Matematika pada Materi Persamaan Kuadrat Menggunakan Teori Newman - Mone, Ariyanti; Napu, Timotius Woda; Lede, Yulius Keremata; Making, Samuel Rex Mulyadi (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to identify the types of errors made by students in solving quadratic equations and analyze the factors that cause them. The research method used is descriptive qualitative with data collection techniques through written tests, interviews, and documentation. The research subjects consisted of 11 students in class IXB of SMP Negeri 1 Loura with instruments in the form of test questions and interview guidelines. The results of the study show that reading errors accounted for 45.45%, characterized by inaccuracies in making assumptions. Errors in understanding the questions also accounted for 45.45%, because students did not write down the known and asked information completely. Question transformation errors reached 81.81%, where students were inaccurate in writing down the mathematical model or did not write it down at all. Process skill errors also accounted for 81.81%, characterized by incorrect calculations and incomplete work. At the stage of writing the final answer, all students (100%) did not write the conclusion or answer correctly. These findings indicate that the dominant errors were in question transformation, process skills, and writing the final answer. The main factors causing these errors were a lack of conceptual understanding, lack of focus, and low accuracy among students. Therefore, a learning strategy that emphasizes understanding the concept of quadratic equations and accustoming students to writing down the steps to solve the problem in sequence is needed.